2010
DOI: 10.1177/0165025409360304
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to variations in academic trajectories amongst recent immigrant youth

Abstract: Immigration presents both challenges and opportunities that affect students’ academic achievement. Over the course of five years, varying academic trajectories were identified for recent immigrant students from Central America, China, the Dominican Republic, Haiti, and Mexico. Latent class growth curve analysis revealed that although some students performed at high or improving levels over time, others showed diminishing performance. Multinomial logistic regressions identified significant group differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Supporting such qualitative research, trajectories of ethnically diverse adolescents living in the U.S. suggest that girls report higher educational expectations in early adolescence and a slower decline in late adolescence as compared to boys (Mello, 2008). Another related body of research, focused on recent Hispanic and Asian immigrants, notes that adolescent girls, as compared to boys, report higher GPAs (Hagelskamp, Suarez-Orozco, & Hughes, 2010) and more stable trajectories of educational performance (i.e., GPA; Suarez-Orozco, Bang, & Onaga, 2010). Sex differences for Mexican-origin adolescents' educational expectations trajectories have been scarcely explored, though the results of previous qualitative (Qin-Hilliard) and quantitative (Mello; Suarez-Orozco et al) studies guide our hypothesis that Mexican-origin girls will show higher and more stable educational expectations as compared to boys.…”
Section: Educational Expectations and Adolescents' Social Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting such qualitative research, trajectories of ethnically diverse adolescents living in the U.S. suggest that girls report higher educational expectations in early adolescence and a slower decline in late adolescence as compared to boys (Mello, 2008). Another related body of research, focused on recent Hispanic and Asian immigrants, notes that adolescent girls, as compared to boys, report higher GPAs (Hagelskamp, Suarez-Orozco, & Hughes, 2010) and more stable trajectories of educational performance (i.e., GPA; Suarez-Orozco, Bang, & Onaga, 2010). Sex differences for Mexican-origin adolescents' educational expectations trajectories have been scarcely explored, though the results of previous qualitative (Qin-Hilliard) and quantitative (Mello; Suarez-Orozco et al) studies guide our hypothesis that Mexican-origin girls will show higher and more stable educational expectations as compared to boys.…”
Section: Educational Expectations and Adolescents' Social Positionmentioning
confidence: 99%
“…For example, prior research suggests that Mexican immigrant parents uphold more traditional gender role attitudes, as compared to later-generation parents, and, as a result, give sons more freedom than daughters (Leaper & Valin, 1996; Rafaelli & Ontai, 2004). This gendered pattern has been offered as a reason why girls outperform boys in academic achievement (Qin-Hilliard, 2003; Suarez-Orozco et al, 2010). However, immigrant parents' more traditional attitudes also have been linked to girls' increased pressure to remain close to the family after high school graduation (Sy & Romero, 2008).…”
Section: Educational Expectations and Adolescents' Social Positionmentioning
confidence: 99%
“…For those families who were separated, 28% had separations from fathers that lasted more than 4 years. Notably, the LISA study found that immigrant youth who underwent protracted family separations and complicated reunifications were at higher risk to show a pattern of declining academic achievement over time once they resettled in the new country (Suárez-Orozco et al, 2010a).…”
Section: Immigration and The Familymentioning
confidence: 99%
“…Some school-based recommendations to support immigrant and refugee students are: hiring bilingual teachers, which can provide benefits to both English language learners and native English speakers (Hernandez, Denton, Macartney, & Blanchard, 2012), recognizing the challenges immigrant and refugee students and their families face (Suárez-Orozco, Bang, & Onaga, 2010), and enhancing teacher training to identify and support the needs of diverse immigrant and refugee students and families (Takanishi, 2004).…”
Section: Introductionmentioning
confidence: 99%